Odor formation in reused potato processing water: potential causes, VOC markers and sensor needs - Joëlle A. J. Housmans; Imca Sampers (Critical Reviews in Food Science and Nutrition, 2026)

An open, reproducible benchmark of daily CO2 forecasting models with applications to GHG monitoring - Pablo Catret-Ruber; David Garcia-Rodriguez; Domingo J. Iglesias Fuente; Ernesto López-Baeza; J. Javier Samper-Zapater; Juan José Martínez Durá (Environmental Modelling & Software, 2026)

The effects of extender egg yolk concentration, penetrating cryoprotectant (amide only vs. amide + glycerol), and pre-freeze cooling rate on post-thaw quality of stallion sperm - V. Zhidkov; L. Ramirez-Agamez; J. Crowley; J.C. Samper; C.C. Love; C. Hernandez-Aviles (Journal of Equine Veterinary Science, 2025)

Global sensitivity analysis of reactive transport modelling for the geochemical evolution of a high-level radioactive waste repository - J. Samper; C. López-Vázquez; B. Pisani; A. Mon; A.C. Samper-Pilar; F.J. Samper-Pilar (Applied Geochemistry, 2025)

Bio-mediated enhancement of supergene copper mineralization: Evidence from Cu isotope geochemistry - J. Javier Rey-Samper; Ryan Mathur; Fernando Tornos (Geochimica et Cosmochimica Acta, 2025)

Benchmarking of reactive transport codes for 2D simulations with mineral dissolution–precipitation reactions and feedback on transport parameters - J. Poonoosamy; C. Wanner; P. Alt Epping; J. F. Águila; J. Samper; L. Montenegro; M. Xie; D. Su; K. U. Mayer; U. Mäder; L. R. Van Loon; G. Kosakowski (Computational Geosciences, 2021)

Toward a Coordinated Global Observing System for Seagrasses and Marine Macroalgae - J. Emmett Duffy; Lisandro Benedetti-Cecchi; Joaquin Trinanes; Frank E. Muller-Karger; Rohani Ambo-Rappe; Christoffer Boström; Alejandro H. Buschmann; Jarrett Byrnes; Robert G. Coles; Joel Creed; Leanne C. Cullen-Unsworth; Guillermo Diaz-Pulido; et al. (Frontiers in Marine Science, 2019)

Demonstrative actions of spring restoration and groundwater protection in rural areas of Abegondo (Galicia, Spain) - A. Naves; J. Samper; A. Mon; B. Pisani; L. Montenegro; J. M. Carvalho (Sustainable Water Resources Management, 2019)

Seagrass Organic Carbon Stocks Show Minimal Variation Over Short Time Scales in a Heterogeneous Subtropical Seascape - Jimena Samper-Villarreal; Peter J. Mumby; Megan I. Saunders; Chris Roelfsema; Catherine E. Lovelock (Estuaries and Coasts, 2018)

Freedom from Tritrichomonas foetus infection in cattle in St. Kitts - Kimberly E. Coker; Joseph J. Lim; Rebecca L. Schleisman; Christopher Vosloo; Hilari M. French; Juan C. Samper; John J. Callanan; Robert O. Gilbert; Fortune Sithole; Chaoqun Yao; Aspinas Chapwanya (Tropical Animal Health and Production, 2018)

Organic carbon in seagrass sediments is influenced by seagrass canopy complexity, turbidity, wave height, and water depth - Jimena Samper‐Villarreal; Catherine E. Lovelock; Megan I. Saunders; Chris Roelfsema; Peter J. Mumby (Limnology and Oceanography, 2016)
Seagrass meadows are important marine carbon sinks, yet they are threatened and declining worldwide. Seagrass management and conservation requires adequate understanding of the physical and biological factors determining carbon content in seagrass sediments. Here, we identified key factors that influence carbon content in seagrass meadows across several environmental gradients in Moreton Bay, SE Queensland. Sampling was conducted in two regions: (1) Canopy Complexity , 98 sites on the Eastern Banks, where seagrass canopy structure and species composition varied while turbidity was consistently low; and (2) Turbidity Gradient , 11 locations across the entire bay, where turbidity varied among sampling locations. Sediment organic carbon content and seagrass structural complexity (shoot density, leaf area, and species specific characteristics) were measured from shallow sediment and seagrass biomass cores at each location, respectively. Environmental data were obtained from empirical measurements (water quality) and models (wave height). The key factors influencing carbon content in seagrass sediments were seagrass structural complexity, turbidity, water depth, and wave height. In the Canopy Complexity region, carbon content was higher for shallower sites and those with higher seagrass structural complexity. When turbidity varied along the Turbidity Gradient , carbon content was higher at sites with high turbidity. In both regions carbon content was consistently higher in sheltered areas with lower wave height. Seagrass canopy structure, water depth, turbidity, and hydrodynamic setting of seagrass meadows should therefore be considered in conservation and management strategies that aim to maximize sediment carbon content.

Light history-dependent respiration explains the hysteresis in the daily ecosystem metabolism of seagrass - Matthew P. Adams; Angus J. P. Ferguson; Paul S. Maxwell; Brodie A. J. Lawson; Jimena Samper-Villarreal; Katherine R. O’Brien (Hydrobiologia, 2016)

Anticipative management for coral reef ecosystem services in the 21st century - Alice Rogers; Alastair R. Harborne; Christopher J. Brown; Yves‐Marie Bozec; Carolina Castro; Iliana Chollett; Karlo Hock; Cheryl A. Knowland; Alyssa Marshell; Juan C. Ortiz; Tries Razak; George Roff; et al. (Global Change Biology, 2015)
Under projections of global climate change and other stressors, significant changes in the ecology, structure and function of coral reefs are predicted. Current management strategies tend to look to the past to set goals, focusing on halting declines and restoring baseline conditions. Here, we explore a complementary approach to decision making that is based on the anticipation of future changes in ecosystem state, function and services. Reviewing the existing literature and utilizing a scenario planning approach, we explore how the structure of coral reef communities might change in the future in response to global climate change and overfishing. We incorporate uncertainties in our predictions by considering heterogeneity in reef types in relation to structural complexity and primary productivity. We examine 14 ecosystem services provided by reefs, and rate their sensitivity to a range of future scenarios and management options. Our predictions suggest that the efficacy of management is highly dependent on biophysical characteristics and reef state. Reserves are currently widely used and are predicted to remain effective for reefs with high structural complexity. However, when complexity is lost, maximizing service provision requires a broader portfolio of management approaches, including the provision of artificial complexity, coral restoration, fish aggregation devices and herbivore management. Increased use of such management tools will require capacity building and technique refinement and we therefore conclude that diversification of our management toolbox should be considered urgently to prepare for the challenges of managing reefs into the 21st century.

Comparative assessment of climate change and its impacts on three coastal aquifers in the Mediterranean - T. Y. Stigter; J. P. Nunes; B. Pisani; Y. Fakir; R. Hugman; Y. Li; S. Tomé; L. Ribeiro; J. Samper; R. Oliveira; J. P. Monteiro; A. Silva; et al. (Regional Environmental Change, 2014)

Inverse modeling of groundwater flow in the semiarid evaporitic closed basin of Los Monegros, Spain - F. J. Samper-Calvete; M. A. García-Vera (Hydrogeology Journal, 1998)

Evaluation of alternative nitrogen and carbon sources for sugarbeet suspension culture platings in development of cell selection schemes - J. W. Saunders; C. J. Tsai; E. Samper (In Vitro Cellular & Developmental Biology - Plant, 1997)